2020
DOI: 10.1007/s12094-020-02381-z
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 transmission, outcome and associated risk factors in cancer patients at the first month of the pandemic in a Spanish hospital in Madrid

Abstract: Background There are no large reported series determining the Covid-19 cancer patient's characteristics. We determine whether differences exist in cumulative incidence and mortality of Covid-19 infection between cancer patients and general population in Madrid. Material and methods We reviewed 1069 medical records of all cancer patients admitted at Oncology department between Feb 1 and April 7, 2020. We described Covid-19 cumulative incidence, treatment outcome, mortality, and associated risk factors. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(149 citation statements)
references
References 9 publications
3
124
1
5
Order By: Relevance
“…Analysis of comorbidities showed a striking prevalence of hypertension in patients with cancer and SARS-CoV-2 Studies have shown that among patients with COVID-19, patients with comorbidities had poorer clinical outcomes than patients without comorbidities. 3,[10][11][12][13][14] On analyzing specific comorbidities, research has shown that hypertension is most associated with the occurrence of severe disease in patients with COVID-19. 15 The correlation between hypertension and ACE-2 receptor expression has been studied 16 and provides clinical insight for patients with hypertension developing more severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of comorbidities showed a striking prevalence of hypertension in patients with cancer and SARS-CoV-2 Studies have shown that among patients with COVID-19, patients with comorbidities had poorer clinical outcomes than patients without comorbidities. 3,[10][11][12][13][14] On analyzing specific comorbidities, research has shown that hypertension is most associated with the occurrence of severe disease in patients with COVID-19. 15 The correlation between hypertension and ACE-2 receptor expression has been studied 16 and provides clinical insight for patients with hypertension developing more severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hematologic and solid tumors can increase the risk of various infections due to neutropenia, lymphopenia, disruption of anatomical surfaces (such as the nasal mucosa), splenic and humoral defects, and the administration of cytotoxic or other immune-suppressive therapies (Rolston, 2017;Safdar and Armstrong, 2011). This immune suppression could be one of the factors implicated in the increased risk of infection by SARS-CoV-2 of patients with cancer (Liang et al, 2020;Rogado et al, 2020). Of particular interest to physicians is whether cytotoxic chemotherapy agents and targeted therapies could potentiate these SARS-CoV-2-related risks and whether certain anti-cancer therapies need to be withheld.…”
Section: Sars-cov-2 Structure and Internalizationmentioning
confidence: 99%
“…Interplay of SARS-CoV-2 and Cancer Biology: Risks and Opportunities Multiple pieces of evidence have indicated an interplay between the biology of SARS-CoV-2 and cancer (Box 1). Evidence suggests that patients with cancer are more likely to be infected by SARS-CoV-2 (Liang et al, 2020;Rogado et al, 2020), more likely develop a severe COVID-19 infection (Garassino et al, 2020;Kuderer et al, 2020;Westblade et al, 2020), and more likely to die as a result of COVID-19 (Garassino et al, 2020;Kuderer et al, 2020;Saini et al, 2020;Westblade et al, 2020;Williamson et al, 2020). In contrast, certain anti-neoplastic hormonal treatments have been suggested to potentially play a protective role in patients with SARS-CoV-2 infections (Stopsack et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Early data from China demonstrated that patients with cancer had a higher mortality rate, compared to patients without cancer [13]. These findings have been supported by more recent data from Europe and the United States [14][15][16]. It was therefore deemed critical to implement effective, primary preventive measures to reduce exposure and minimise risk for patients with cancer.…”
Section: Introductionmentioning
confidence: 98%